Elastic displacement spectrum-based design of damage-controlling BRBFs with rocking walls. (September 2018) - Feng, Yulong; Zhang, Zhi; Chong, Xun; Wu, Jing; Meng, Shaoping
Abstract: This paper investigates the seismic design and performance of buckling-restrained braced frames with rocking walls (BRBF-RWs) for the purpose of using rocking walls (RWs) to mitigate the drift concentration issue of buckling-restrained braced frames (BRBFs). Formulas for calculating the elastic structural lateral displacement and RW internal force under typical lateral loads are derived and validated; then, the stiffness and strength demand of the RW are approximately determined based on the elastic formulas when the BRBF-RW enters the inelastic stage. Combined with the proposed inelastic demand, an elastic displacement spectrum-based design procedure is presented, which can directly determine the sectional area of the buckling-restrained braces (BRBs) and the required stiffness and strength of the RW. A 6-story steel BRBF-RW is designed using the proposed procedure as an example, and a series of nonlinear pushover analyses (NPAs) and nonlinear response history analyses (NRHAs) are performed to validate the design. The example shows that the designed target displacement and the NRHA result are close and that the deviations between the drift concentration factor, RW maximum moment and shear force obtained using formulas and using NPAs and NRHAs are small. Lastly, a brief comparative analysis is performed to illustrate the enhanced seismic performance of the designed BRBF-RW via NPAs and NRHAs. Highlights: Elastic formulas for BRBF-RW lateral displacement and RW internal force under typical lateral loads are derived and validated. Formulas for RW stiffness and strength demand when the BRBF-RW enters the inelastic stage are proposed and validated. An elastic displacement spectrum-based design procedure for BRBF-RWs is presented and validated. Enhanced seismic performance of the designed BRBF-RW is illustrated through a comparison to BRBF, RWF and MRF.